Peranan Nazhir Wakaf Dalam Perspektif Hukum Islam dan Undang - Undang No. 41 Tahun 2004 di KUA Kecamatan Candiroto - Muh. Syakur; Triyono; Eko Sariyekti (Yayasan Azhar Amanaa Yogyakarta, 2023)
This study examines the role of waqf nazhir at the Candiroto District Religious Affairs Office (KUA) from the perspective of Islamic law and Law Number 41 of 2004 on Waqf. Nazhir is responsible for managing and developing waqf assets in accordance with the purpose of the endowment, while ensuring compliance with both Islamic legal principles and national regulations. This research employs a qualitative approach through field studies, using observation, interviews, and documentation as data collection techniques involving KUA officials and waqf nazhirs in the region. Data were analyzed inductively to gain an in-depth understanding of waqf management practices. The findings indicate that the nazhirs at KUA Candiroto District generally carry out their duties, responsibilities, and authorities in accordance with Islamic law on waqf. However, the implementation of Law Number 41 of 2004 has not been fully achieved, particularly in administrative matters and in submitting regular reports on waqf development. This condition is influenced by the limited understanding of the nazhirs regarding the regulation, suggesting the need for capacity building and continuous guidance to ensure that waqf management becomes more optimal and complies with existing legal provisions.